A balada do homem abatido: um estudo comparativo entre Os ratos e Angústia - Salgado, Marcus Rogério Tavares Sampaio (Navegações, 2017)
O artigo propõe um estudo comparativo entre os romances Os ratos (Dyonélio Machado) e Angústia (Graciliano Ramos), a partir da investigação de três eixos críticos: a) a tematização do ato de deambular; b) a presença de estratégias estéticas características do expressionismo; c) a recorrência do super-signo do rato. ******************************************************************** The ballad of the beaten man: a comparative study between Os ratos and Angústia Abstract: The article is a comparative study between the novels Os ratos (Dyonélio Machado) e Angústia (Graciliano Ramos), out of three main critical points: a) thematizing of the act of strolling; b) presence of aesthetical strategies typical of expressionism; c) occurring of the rat as a supersign. Keywords: Brazilian literature; comparative studies; expressionism.